2018
DOI: 10.1371/journal.pone.0202976
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding by capture using a single COI probe (MCSP) to identify and quantify fish species in ichthyoplankton swarms

Abstract: The ability to determine the composition and relative frequencies of fish species in large ichthyoplankton swarms could have extremely important ecological applications However, this task is currently hampered by methodological limitations. We proposed a new method for Amazonian species based on hybridization capture of the COI gene DNA from a distant species (Danio rerio), absent from our study area (the Amazon basin). The COI sequence of this species is approximately equidistant from all COI of Amazonian spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 56 publications
1
48
0
Order By: Relevance
“…This observation reinforces the idea that more sequences of fish species must be deposited in databases, especially in river basins with rich fish fauna as the Upper Paraná River. Another positive aspect is that, compared with DNA barcoding (Arroyave and Stiassny 2014, Becker et al 2015, Frantine-Silva et al 2015, our method can trigger significant advances in the quality of ecological studies in fish, as observed in some recent studies with metabarcoding (Guillerault et al 2017, Maggia et al 2017, Mariac et al 2018, Barbato et al 2019 and, mainly, to ensure significant reduction in labor time and cost per specimen reaching 80% of reduction (Shokralla et al 2015). Despite some differences in obtaining DNA samples, both environmental DNA (eDNA) and DNA metabarcoding from bulk samples are subject to false negatives and false positives (Ficetola Gentile et al 2015Gentile et al , 2016Divoll et al 2018).…”
Section: Species Identificationmentioning
confidence: 99%
See 3 more Smart Citations
“…This observation reinforces the idea that more sequences of fish species must be deposited in databases, especially in river basins with rich fish fauna as the Upper Paraná River. Another positive aspect is that, compared with DNA barcoding (Arroyave and Stiassny 2014, Becker et al 2015, Frantine-Silva et al 2015, our method can trigger significant advances in the quality of ecological studies in fish, as observed in some recent studies with metabarcoding (Guillerault et al 2017, Maggia et al 2017, Mariac et al 2018, Barbato et al 2019 and, mainly, to ensure significant reduction in labor time and cost per specimen reaching 80% of reduction (Shokralla et al 2015). Despite some differences in obtaining DNA samples, both environmental DNA (eDNA) and DNA metabarcoding from bulk samples are subject to false negatives and false positives (Ficetola Gentile et al 2015Gentile et al , 2016Divoll et al 2018).…”
Section: Species Identificationmentioning
confidence: 99%
“…Quali-and quantitative studies involving metabarcoding and eDNA have increased significantly in recent years (Hänfling et al 2016;Valentini et al 2016;Evans and Lamberti 2017;Yamamoto et al 2017;Nakagawa et al 2018;Mariac et al 2018). However, the reliable quantification of organisms remains a problem (Evans et al 2016;Kelly et al 2017;Hansen et al 2018;Mariac et al 2018). eDNA studies have shown a positive correlation between species-specific DNA concentrations in biomass and abundance in eDNA (Takahara et al 2012;Maruyama et al 2014;Doi et al 2015;Evans et al 2016).…”
Section: Relative Abundancementioning
confidence: 99%
See 2 more Smart Citations
“…Relatively small amounts of starting DNA material are required for this approach (Gnirke et al, ; Hodges et al, ), which has made it advantageous in studies where endogenous DNA content is low and fragment size is small, such as in ancient samples (Enk et al, ). Recently, target capture of mtDNA has been applied to both ancient eDNA from sediment (Slon et al, ) and modern eDNA from water samples (Mariac et al, ; Wilcox et al, ) for species detection. Although a reference genome is required to design capture probes for population genomic analyses, this genome may be sourced from a related species (even a distant one), since a perfect match between the probes and the target DNA is not a strict necessity (Enk et al, ).…”
Section: Future Potential For Population Genetic Analyses Of Nuclear mentioning
confidence: 99%